1996
DOI: 10.1007/bf01999894
|View full text |Cite
|
Sign up to set email alerts
|

Isolated optic neuritis and its prognosis for multiple sclerosis: a clinical and paraclinical study with evoked potentials. CSF examination and brain MRI

Abstract: Our study evaluated the frequency of developing multiple sclerosis (MS) after acute isolated optic neuritis (ON), the possible association with risk factors (gender, age), and the diagnostic and prognosis role of paraclinical tests. We studied 100 ON patients (mean age 28.9 years: SD 8.9): 85 patients were regularly followed up. Sixty-six patients underwent multimodality evoked potential (EP) test, examination and brain MRI within six months of the onset of ON. Over a mean follow-up of 5.2 years, MS occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
6
1
Order By: Relevance
“…Earlier, using conventional evoked potentials, ON patients have been shown to have silent CNS lesions in the somatosensory [13,25], motor [13,25], visual [13], and auditory pathways [13]. Our results, however, suggest that the central sudomotor pathways may also be lesioned in ON patients.…”
Section: Discussioncontrasting
confidence: 50%
“…Earlier, using conventional evoked potentials, ON patients have been shown to have silent CNS lesions in the somatosensory [13,25], motor [13,25], visual [13], and auditory pathways [13]. Our results, however, suggest that the central sudomotor pathways may also be lesioned in ON patients.…”
Section: Discussioncontrasting
confidence: 50%
“…Baseline clinical data have been described in two previous papers [17,32]. The follow-up study was restricted to patients whose paraclinical tests (brain MRI, multiple EPs, CSF examination) had been performed within 6 months of ON onset; 112 cases fulfilled this criterion.…”
Section: Methodsmentioning
confidence: 99%
“…151 However, a more recent study showed some predictive value in the assessment of CSF of patients who have MS. Those who had both abnormal MRI and elevated intrathecal IgG synthesis had an 46% increased risk of developing MS after four years, compared with 33% if they had only an abnormal MRI. 152 Furthermore, a positive ANA did not have any effect on the patient's course or response to any treatment given. 4 Therefore, besides neuroimaging, no further laboratory testing is required for typical optic neuritis.…”
Section: Diagnostic and Prognostic Testsmentioning
confidence: 98%